Photocatalytic reactions of metal diphthalocyanine complexes - Nensala, Ngudiankama (Rhodes University, Faculty of Science, Department of Chemistry, 2000)
Photocatalytic reactions of tin diphthalocyanine, Sn ^IVPcâ‚‚ and anionic form of Nd^III, Dy^III, Eu^III, Tm^III and Lu^III diphthalocyanine complexes ( [Pc(-2)Nd^IIIpc(-2)]â » , [Pc(-2)Dy^IIIPc(-2)]â » , [Pc(-2)Eu^IIIPc(-2)â », [Pc(-2)Tm^IIlPc(-2)r and [Pc(-2)LuIIIpc(-2)]â » respectively) in the presence of CHâ‚‚CIâ‚‚, S0â‚‚, pentachlorophenol (PCP), 4-chlorophenol (4-Cp) and thionyl chloride have been studied. Photoreactions involving lanthanide diphthalocyanines, filtered and unfiltered radiations were employed, whereas for photoreactions involving tin diphthalocyanine, only unfiltered radiation was employed. For lanthanide diphthalocyanine complexes, LnPce-, the photosensitization power increases with the decrease of the lanthanide ionic radii, implying that the photocatalytic activity of LnPcâ‚‚â » complexes is associated with the Ï€-Ï€ interaction between both phthalocyanine rings. Thus, LuPcâ‚‚â » is a better photocatalyst than other lanthanide diphthalocyanine complexes. Photolysis ofSnPcâ‚‚ in an acetonitrile/dichloromethane solvent mixture, using unfiltered radiation from a tungsten lamp, results in the one-electron oxidation of this species to [Pc( -2 )Sn(IV)Pc(-1)]â ». The relative quantum yields for the disappearance of SnPcâ‚‚ are in the order of 10â »Â¹. The photoreaction of SnPcâ‚‚ is preceded by excitation to nÏ€* excited states, before been ,quenched by CHâ‚‚CIâ‚‚. The one-electron oxidation species, [Pc(-2)Sn(lV)pc(-1)]â » was also formed during the photolysis of SnPcâ‚‚ in dichloromethane containing S0â‚‚, and with quantum yields of order of 10â »Â³. Visible photolysis of [Pc( -2)Nd^IIIpc(-2)]â », [Pc(-2)Dy^IIIPc(-2)]â » and [Pc(-2)Lu^IIIpc(-2)]â » in N,N. dimethylformamide (DMF)/dichloromethane solvent mixture containing SOâ‚‚, results in the formation of the one-electron oxidation species, Pc(-2 )Nd^IIIpc(-1), Pc( -2) Dyi^IIIPc(-1) and Pc(-2)Lu^IIIpc(-1), respectively. The relative quantum yields are in the order of 10Â². The photoreactions are preceded by population of the excited triplet state,Â³Ï€-Ï€* [ LnPcâ‚‚]â » complex, before exchanging an electron with S0â‚‚. The one-electron oxidation species of Dy^III and Lu^III diphthalocyanine complexes have also been formed from visible photolysis of [Pc(-2 )Dy^IIIPc(-2)]â »and [Pc(-2)Lu^IIIpc(-2)]â »in acetonitrile containing PCP. The PCP is reductively dechlorinated to tetra- and trichlorophenols. The quantum yields for the photosensitization reactions are in the order of 1 0â ». Photolysis, using visible radiation from 220 W Quartzline lamp, of an aqueous solution of 4-Cp, saturated with oxygen and containing a suspension of solid [Pc(-2)Nd^IIIpc(-2)]â », results in the formation of benzoquinone, hydro quinone and 4-chlorocatechol. The quantum yields for the degradation of 4-Cp are in the order of 10â ». Langmuir-Hinshelwood kinetic model shows the adsorption of 4-chlorophenol onto solid [Pc(-2)Nd^IIIpc(-2)]â ». Lanthanide diphthalocyanine complexes ([Pc-2)Nd^IIIpc(-2)]â ». [Pc(-2)Eu^IIIpc(-2)]â », (Pc(-2)Tm^IIIpc( -2)]â » and (Pc(-2)Lu^IIIpc(-2)]â ») undergo one or two-electron oxidation in the presence of thionyl chloride. At low concentrations of SOCIâ‚‚(<10â »â ´ mol dmâ »Â³) the visible yhotolysis of [Pc(-2 )LnPc(-2)]â » complexes result in the one-electron oxidation, giving neutral lanthanide diphthalocyanine species, Pc(-2)Ln^IIIpc(-1). The Pc(-2 )LnPc(-I) species undergoes one-electron photooxidation to [Pc(-I )LnPc( -I)]â » in dichloromethane and in the presence of SOCâ‚ â‚‚. At large concentrations of SOCâ‚ â‚‚ (>10â »Â² mol dmâ »Â³), direct two-electron oxidation of the (Pc(-2 )LnPc - 2)]â » species to (Pc(-1)LnPc(-1)]â » occurs. Spectroelectrochemical behaviours of Sn^IVPcâ‚‚ have been also studied. The cyclic voltammetry ofSnPcâ‚‚ in CHâ‚‚CIâ‚‚/TBAP show two reduction couples at -0.56 V and -0.89 V versus saturated calomel electrode (SCE) and one oxidation couple at 0.35 V versus SCE. In DMFITEAP system, the reduction couples are observed at -0.44 V and -0.81 V versus SCE whereas the oxidation couple occurred at 0.43 V versus SCE. The oxidation couple corresponds to [Pc(-2 )Sn^IVPc(-2 )]/[Pc(-2)Sn^IVPc( -I)] . and the reduction couples to [Pc(-2)Sn^IVPc( -2 )]/[Pc(-2 )Sn^IVPc( -3 )]â » and [Pc(-2)Snl^IVPc( -3)] â »/[Pc(-3 )Sn^IVPc(-3)]Â²â », respectively. The electronic absorption spectra of these reduced and oxidized species are reported.
Keywords: Metal complexes; Electrochemistry; Photochemistry; Pentachlorophenol